Control, innovation and international joint venture performance : The moderating role of internal and external environments - Nguyen, Huu Le; Larimo, Jorma; Wang, Yi (Elsevier, 2019)
This study aims to analyze how parent control strategies affect the degree of innovation in international joint ventures (IJVs) and how different types of innovation strategies - divided into radical and incremental innovation strategies - influence the performance of IJVs. This study uses the most widely adopted definition and operationalization of control in IJVs by Geringer and Hebert (1989), including the three dimensions: mechanisms, focus, and extent of control. These relationships are further analyzed by integrating internal and external moderating factors and their connections with IJV performance. Our theoretical analysis proposes that various control strategies differently influence an IJV’s innovation activities under various internal environmental moderating factors. These, in turn, differently influence the IJV performance. Furthermore, we suggest that the external environmental factors moderate the relationship between innovation strategies and performance of IJVs.
Keywords: Control strategies; Incremental and radical innovation; Performance; International joint ventures; innovaatiot; innovatiivisuus; uutuudet; fi=Kansainvälinen liiketoiminta|en=International Business|